2018
DOI: 10.1002/aoc.4282
|View full text |Cite
|
Sign up to set email alerts
|

Pd(0)‐ S‐propyl‐2‐aminobenzothioate immobilized onto functionalized magnetic nanoporous MCM‐41 as efficient and recyclable nanocatalyst for the Suzuki, Stille and Heck cross coupling reactions

Abstract: The present work describes the use of Pd(0)-S-propyl-2-aminobenzothioate Complex immobilized onto functionalized magnetic nanoporous MCM-41(Fe 3 O 4 @MCM-41@Pd-SPATB) as efficient and recyclable nano-organometallic catalyst for C-C bond formation between various aryl halides with phenylboronic acid (Suzuki reaction), aryl halides with triphenyltin chloride (Stille reaction), and aryl halides with n-butyl acrylate (Heck reaction). All the reactions were carried out in PEG-400 as green solvent with short reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…Melting point measured literature 1 60 98 61-63 62-64 [28] 2 100 96 43-44 43-45 [28] 3 160 97 81-83 82-85 [28] 4 200 90 Oil Oil [60] 5 160 87 62-64 62-64 [28] 6 120 95 43-45 43-45 [28] 7 80 88 84-86 82-84 [28] 8 300 90 72-73 70-72 [60] 9 50 94 111-113 111-114 [28] (Continues)…”
Section: Entryunclassified
“…Melting point measured literature 1 60 98 61-63 62-64 [28] 2 100 96 43-44 43-45 [28] 3 160 97 81-83 82-85 [28] 4 200 90 Oil Oil [60] 5 160 87 62-64 62-64 [28] 6 120 95 43-45 43-45 [28] 7 80 88 84-86 82-84 [28] 8 300 90 72-73 70-72 [60] 9 50 94 111-113 111-114 [28] (Continues)…”
Section: Entryunclassified
“…The TGA of the synthesized Fe 3 O 4 @silica‐MCM‐41@DABCO indicates 6% weight loss between 47 and 150°C in one step attributable to desorption of H 2 O. The other weight losses are in the regions 150–250°C (about 1.54%), 250–450°C (11%) and 450–600°C (7%) mainly related to the removal of physisorbed solvent and H 2 O hosted inside the nanopore channels of the MCM‐41 network, the decomposition of organic moieties on the surface of Fe 3 O 4 @MCM‐41@DABCO and condensation of the Si‐OH silanol agents, respectively …”
Section: Resultsmentioning
confidence: 99%
“…Despite their superior features, due to poor morphology, low thermal stability, high aggregation tendency and susceptibility to oxidation of these bare materials, polymers, carbon layers and silicate materials are utilized to coat such magnetic nanoparticles. Mesoporous silicate coatings, by preventing the aggregation of nanoparticles, can improve the characteristics of magnetic nanostructures due to their biocompatibility, small nanopore size, controllable morphologies, high surface area, chemical stability and inertness, and can be widely utilized as heterogeneous catalysts in organic transformations . In order to recover the catalysts based on silica‐MCM‐41 from reaction mixtures, functionalized magnetic nanoparticles with mesoporous silica coating have been developed as a powerful tool .…”
Section: Introductionmentioning
confidence: 99%
“…The same research group also reported a Pd(0)-S-propyl-2-aminobenzothioate complex immobilized onto functionalized magnetic MCM-41(Fe3O4@MCM-41@Pd-SPATB) as an efficient and recyclable nano-organometallic catalyst for Suzuki, Stille and Heck reactions [166]. For the preparation of Fe3O4@MCM-41@Pd-SPATB ( Figure 63), Fe3O4@MCM-41 was functionalized with (3mercaptopropyl)trimethoxysilane (MPTMS) and, afterwards, with S-propyl-2-aminobenzothioate, providing the denoted Fe3O4@MCM-41@SPATB.…”
Section: Magnetic Mcm-41 To Incorporate Metal Nanoparticlesmentioning
confidence: 97%